Analisis Prediksi Motion Sickness Incidence (MSI) Pada Kapal Penyeberangan Di Perairan Makassar - Ishak Bawias; Fitria Lungari; Risal Risal (Departemen Teknik Kelautan Universitas Hasanuddin, 2022)
Motion sickness on ships is also known as seasickness. It is a symptom of illness caused by the movement of the vessel, which results in uncomfortable physical symptoms characterized by difficulty breathing, dizziness, nausea, paleness, and vomiting. The main cause of seasickness is the absence of similarity of excitability or conformity between the stimulus, eye, and ear labyrinth the human brain receives. The direction of the waves is very influential on the stability of the ship being boarded or not. The research method uses ship motion software simulation. The study results concluded that the vessel's condition was stable, indicated by the waves coming from the 0° or the ship's state sailing in the direction of the incoming waves. Thus, it is predicted that no passengers will experience motion sickness. Meanwhile, the unstable condition of the ship is indicated by the ship with a wave direction of 180° or the state of the vessel sailing in the opposite direction to the direction of the wave. So it is predicted that passengers will experience seasickness after 2 hours of travel.